Inter-firm Trust between Emerging Markets: Chinese Firms in Africa. (September 2019) - Elliot, Esi A.; Zhu, Zhen; Wang, Fei-Ling
The rapid global expansion of marketers from one emerging market to another such as countries in Africa, Latin America, Central Asia, and the Middle East is dramatically changing the landscape of international business relationships. A leading example is Chinese firms in African countries. The element of trust is highlighted in such emerging market relationships that involve large investments from multiple constituents with diverging and sometimes conflicting objectives. Our study provides a broader, more encompassing macromarketing framework by investigating inter-firm trust between two emerging markets from an institutional perspective. Our study develops the inter-firm trust concept in the context of Chinese businesses in Africa on the bases of extant literature, field interviews, and observations focused mainly on three African countries (Ghana, Kenya and South Africa). Drawing from trust theory and institutional theory, our study reveals three dimensions for the inter-firm trust concept and both trustor and trustee factors influence the perception of Chinese businesses in Africa. Macromarketing and practical implications for building and managing inter-firm trust at a multi-level between emerging markets are also discussed.